Factors associated with knowledge and attitude of breastfeeding among staff of Faculty of Medicine and Health Sciences, Universiti Putra Malaysia - Ramzaa, Wan Iffah Afiqah; Sugumar, Mogana; Ahmad, Norliza; Lim, Poh Ying (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Many studies have investigated the knowledge and attitude towards breastfeeding among fathers and mothers, however studies looking at working adults’ knowledge and attitude towards breastfeeding is limited. Working adults with good knowledge and favourable attitude toward the practice of breastfeeding may increase the breast-feeding initiative among working mothers. Therefore, the objective of this study was to investigate the knowledge and attitude toward breastfeeding among staff from the Faculty of Medicine and Health Sciences of a public university and its associated factors. Methods: A cross sectional study was conducted among faculty staff members. The respondents were selected by simple random sampling and a self-administered questionnaire was used to investigate the knowledge and attitude towards breastfeeding among them. Multiple linear regression was used to determine the factors associated with knowledge and attitude respectively. Results: A total of 117 respondents were recruited to take part in this study. Of these, 83(70.9%) had good knowledge while 61(52.6%) respondents had favourable attitude toward breastfeeding. There was significant positive fair correlation between knowledge and attitude score (r=0.396,p<0.001). Gender (coefficient:1.04,CI:0.25-1.84), education level (coefficient:1.56,CI:0.60-2.53) and number of children (coefficient:0.21,CI:0.01-0.40) were the factors affecting knowledge score whereas education level (coefficient:5.73,CI:1.40-10.07) and number of children (coefficient:1.3,CI:0.41-2.11) were the factors affecting attitude. Conclusion: Overall, majority of respondents were found to have good knowledge but half of them had favourable attitude toward breastfeeding. A awareness program is suggested particularly for male, low education level and those with less number of children in order to increase knowledge and attitude toward breastfeeding.